Oxygenation of hydrocarbons by cytochrome P-450 model compounds: modification of reactivity by axial ligands. - Collman, J P (1983)
The rate of olefin oxygenation catalyzed by synthetic metalloporphyrins is examined, employing sodium hypochlorite as the oxygen atom source. The rate of epoxidation and the stability of the catalyst are shown to be dependent on the nature of the axial ligand employed. A rationale for this effect is presented and analogy is made to the role of the thiolate ligand in cytochrome P-450.